Phosphorus recovery using a struvite crystallization process - MueangSai, Arunee; Sangsawang, Aditaya; Limkhuansuwan, Vassanasak; Suanboon, Yaowaret (Agriculture & Technology RMUTI Journal, 2024)
Struvite in wastewater of industrial process is part of the cause of blocking in the pipes line of the wastewater treatment system, the cost increases and wastes more time to solve the problem. On the other hand, considering the composition of struvite, it contains phosphorus, which can be used as a fertilizer and valuable in agriculture. Therefore, this research was to study the optimum conditions of the chemical crystallization process of struvite in the wastewater from a cassava ethanol production plant. The properties of wastewater and optimum conditions for the crystallization of struvite, including the pH and the molar ratio of magnesium to phosphorus (Mg:P), were identified. The properties of wastewater showed that the average value of pH was 4.32. While Mg, NH3, and P were 4,192.5, 347.2, and 267.33 milligrams per liter (mg/L), respectively. The filtered and unfiltered wastewater tests found that filtered wastewater sludge contained struvite and was less contaminated with other organic matter. Therefore, it was used to crystallize struvite. The result found that pH at 9.5, 10, and 11 performed quite a lot of crystallization of struvite. However, the optimum pH was at pH 10 since it can reclaim more than 98% phosphorus. Testing the ratio between magnesium and phosphorus (Mg:P) found that at pH 9.5, the proportion of struvite crystallization was also increased. At the proportion 1:1 to 5:1, struvite crystals grew from 124.10 mg/L to 213.80 mg/L. The optimum condition found in this study was the ratio of 5:1 at pH 9.5, which increased the crystallization of struvite, and the phosphorus reversal was more than 97%, helping to bring back phosphorus from wastewater to use in agriculture.